A Drosophila model of FUS-related neurodegeneration reveals genetic interaction between FUS and TDP-43. - Lanson, N.A.; Maltare, A.; King, H.; Smith, R.; Kim, J.H.; Taylor, J.P.; Lloyd, T.E.; Pandey, U.B. (Human Molecular Genetics, 2011)
Amyotrophic lateral sclerosis (ALS) is a late-onset neurodegenerative disorder characterized by the loss of motor neurons. Fused in sarcoma/translated in liposarcoma (FUS/TLS) and TAR DNA-binding protein (TDP)-43 are DNA/RNA-binding proteins found to be mutated in sporadic and familial forms of ALS. Ectopic expression of human ALS-causing FUS/TLS mutations in Drosophila caused an accumulation of ubiquitinated proteins, neurodegeneration, larval-crawling defect and early lethality. Mutant FUS/TLS localized to both the cytoplasm and nucleus, whereas wild-type FUS/TLS localized only to the nucleus, suggesting that the cytoplasmic localization of FUS/TLS is required for toxicity. Furthermore, we found that deletion of the nuclear export signal strongly suppressed toxicity, suggesting that cytoplasmic localization is necessary for neurodegeneration. Interestingly, we observed that FUS/TLS genetically interacts with TDP-43 in a mutation-dependent fashion to cause neurodegeneration in vivo. In summary, we demonstrate that ALS-associated mutations in FUS/TLS cause adult-onset neurodegeneration via a gain-of-toxicity mechanism that involves redistribution of the protein from the nucleus to the cytoplasm and is likely to involve an interaction with TDP-43.